2011
DOI: 10.1128/jcm.02381-10
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Cost Analysis of Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry for Routine Identification of Yeast

Abstract: Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry was compared to phenotypic testing for yeast identification. MALDI-TOF mass spectrometry yielded 96.3% and 84.5% accurate species level identifications (spectral scores, >1.8) for 138 common and 103 archived strains of yeast. MALDI-TOF mass spectrometry is accurate, rapid (5.1 min of hands-on time/identification), and cost-effective ($0.50/sample) for yeast identification in the clinical laboratory.Candida is the fourth le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
216
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(236 citation statements)
references
References 30 publications
14
216
1
5
Order By: Relevance
“…Yet, direct identification of environmental yeast isolates by MALDI-TOF MS is still limited. As identification successes obtained for clinical yeast isolates are very promising (Marklein et al 2009;Stevenson et al 2010;van Veen et al 2010;Dhiman et al 2011), an expansion of the database toward environmental isolates is desirable. With these data becoming available, it will be possible to fully exploit the capacity of this rapid and costeffective method for environmental studies.…”
Section: Yeast Identification and Classification By Maldi-tof Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, direct identification of environmental yeast isolates by MALDI-TOF MS is still limited. As identification successes obtained for clinical yeast isolates are very promising (Marklein et al 2009;Stevenson et al 2010;van Veen et al 2010;Dhiman et al 2011), an expansion of the database toward environmental isolates is desirable. With these data becoming available, it will be possible to fully exploit the capacity of this rapid and costeffective method for environmental studies.…”
Section: Yeast Identification and Classification By Maldi-tof Msmentioning
confidence: 99%
“…Furthermore, reference spectra created from measurements of one isolate can be compared with those of other isolates to analyze phylogenetic relationships and thus classify unknown organisms. This mass spectrometric technique has been extensively applied to the study of clinically important yeasts, yielding high rates of correct species-level identifications (e.g., Marklein et al 2009;Stevenson et al 2010;van Veen et al 2010;Dhiman et al 2011). Yet, to our knowledge, it has not been applied to yeasts in the context of ecological studies.…”
Section: Introductionmentioning
confidence: 99%
“…The use of matrixassisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) for the rapid identification of clinical yeast and mycobacterial isolates has been evaluated in some studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, there has been a limited number of direct comparison studies focusing on the performance of the two MALDI-TOF systems to rapidly identify yeast and mycobacterial clinical isolates (26)(27)(28).…”
mentioning
confidence: 99%
“…7 organism collection. It should be noted that whereas the confidence scores of ≥2.0 used for secure species level ID in the present study are those recommended by the manufacturer, other investigators have suggested that this breakpoint may be overly conservative and that lowering the secure species threshold to 1.8 improved species level ID of yeasts from 87%-92% to >99% of isolates while preserving 100% accuracy of IDs (Buchan and Ledeboer, 2013;Dhiman et al, 2011;Stevenson et al, 2010). In another study VanHerendael et al (2012) found that 100% of isolates with lower confidence scores indicating genus only ID were also correctly IDed to species level.…”
Section: Resultsmentioning
confidence: 76%